A case of tumor-like inflammatory demyelinating disease with progressive brain and spinal cord involvement - Peng, Xu Zhi; Hua, Li Hong; Qiang, Sun Zhi; Qiang, Wu (São Paulo Medical Journal, 2015)
CONTEXT: Tumor-like inflammatory demyelinating disease (TIDD) usually occurs in the brain and rarely occurs in the spinal cord. TIDD appears to be very similar to tumors such as gliomas on imaging, which may lead to incorrect or delayed diagnosis and treatment. CASE REPORT: Because of headache and incoherent speech, a 24-year-old Chinese male presented to our hospital with a two-week history of respiratory infections. After dexamethasone treatment, his symptoms still got worse and surgery was performed for diagnostic purposes. Histological examination revealed that the lesion was inflammatory. Further lesions appeared in the spine (T3 and T4 levels) after two months and in the right occipital lobe after three months. After intravenous immunoglobulin (IVIG) and methylpred-nisolone treatment, his symptoms improved. CONCLUSION: Progressive lesions may damage the brain and spinal cord, and long-term prednisolone and IVIG therapy are beneficial in TIDD patients.